Using Google Classroom for Critical Reading Improvement Strategies Skill - Gunaldi Masbiran; Yeni Afriyeni (Journal of English Language and Education, 2022)
Students have problems in reading class. Google Classroom can be use as media in the classroom This classroom action research show that students in STBA Persada Bunda have improved their critical reading strategies. It can be seen from the result of their test for every cylce. Their mark is better than before applying google classroom. Google classroom improved teaching and learning process at the Fourth Semester Students’ of School of Foreign Languages. They are brave enough to ask question, give  comment, got the conclusion about the task given by themselves, and share idea among their friend. The factors the that influence the changes reading comprehension by google classroom, the students knew about topic, main idea, detail which found in the reading text